Journey cake, ho! - Sawyer, Ruth (New York : Puffin Books, 1978)
Johnny is leaving the farm because of hard times when his Journey Cake leads him on a merry chase that results in a farm yard full of animals and the family together again.
Caldecott Honor Book
Keywords: Folklore - United States